Análisis de la percepción de los agricultores de maíz sobre la calidad de vida en el recinto Las Pampas, cantón Palenque provincia de Los Ríos - Chimbolema Llagsha, Jhonatan Javier (2023)
The following study focuses on the analysis of perception amongst corn farmers in Las Pampas, located in Palenque, Los Rios province, in relation to quality of life. The research develops its applicative basis in development theory which shares, among different measures, applied sustainability to the living conditions of the specified region. To reach this objective mixed methodology was conducted que combined qualitative and quantitive techniques in order to gather and analyze data through surveys and an interview. The results reveal factors such as, food security, urgent access to basic services, working conditions, and self-development. The document concludes that, to understand the quality of life of the families there involved in the study, future studies should integrate, measuring tools to the variables to obtain qualifiable independent tracking for the focus of the methodology. The research regarding the quality of life of the mentioned community, prompts the researcher to include adapted strategies of education models for significant improvement and likewise that in future research government attention may be harnessed for similar locations, not only in subjective dimensions of individuals and their quality of life but also objectively and for their integral development. In this way the document highlights the lack of recognition for farmers and the methods towards sustainable development and other actions. The importance of applying existing measurements and techniques such as adaptable surveys by the WHO (World Health Organization).